2002
DOI: 10.1113/jphysiol.2002.024281
|View full text |Cite
|
Sign up to set email alerts
|

Role of the flocculus in mediating vestibular nucleus neuron plasticity during vestibular compensation in the rat

Abstract: We investigated the role of the cerebellar flocculus in mediating the adaptive changes that occur in the intrinsic properties of brainstem medial vestibular nucleus (MVN) neurons during vestibular compensation. Ipsi-lesional, but not contra-lesional, flocculectomy prevented the compensatory increase in intrinsic excitability (CIE) that normally occurs in the de-afferented MVN neurons within 4 h after unilateral labyrinthectomy (UL). Flocculectomy did not, however, prevent the down-regulation of efficacy of GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 45 publications
(76 reference statements)
2
42
0
1
Order By: Relevance
“…Overall, our results agree with the proposal that the vestibular compensation process consists of independent cellular plastic mechanisms, which display different dependencies on cerebellar inputs (Johnston et al 2002;see Paterson et al 2006 for a review).…”
Section: Influence Of the Cerebellum On The Intrinsic Cellular Plastisupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, our results agree with the proposal that the vestibular compensation process consists of independent cellular plastic mechanisms, which display different dependencies on cerebellar inputs (Johnston et al 2002;see Paterson et al 2006 for a review).…”
Section: Influence Of the Cerebellum On The Intrinsic Cellular Plastisupporting
confidence: 82%
“…While the vestibular cerebellum's role in motor leaning is well established, only a few investigations have explicitly addressed whether this region plays a comparable role in the vestibular compensation process following peripheral lesions (Johnston et al 2002;Kitahara et al 1998a). Nevertheless, the evidence that is available to date supports the proposal that the floccular complex plays a comparable role during VOR postlesional recovery and motor learning.…”
Section: Introductionmentioning
confidence: 82%
“…An important role for the flocculus is also indicated by the finding that in a knockout mouse lacking the delta-2 subunit of the glutamate receptor, which is selectively localized in cerebellar Purkinje cells and which is essential for cerebellar cortical plasticity, the severity of ocular nystagmus after UVD is exaggerated, and the time course of recovery is prolonged [45] . Consistent with this are the findings that indicate that cerebellar cortical plasticity in the flocculus occurs after UVD, and is required for compensation [46][47][48][49][50] . However, the flocculus is not essential for VC, as even in flocculectomized animals the ocular nystagmus eventually disappears completely; thus, other processes, such as the changes in intrinsic properties of MVN neurons, and synaptic reorganization of the brainstem vestibular pathways, may be sufficient to achieve compensation but over a longer recovery time.…”
Section: Postlesional Changes In the Control Of Vn Neurons By The Cersupporting
confidence: 74%
“…Early after UVD inhibitory signals from the flocculus to the VN are in fact decreased ipsilesional and increased contralesional in rats [49,50]. Yet, the specific role of the vestibulo-cerebellum itself remains nevertheless speculative, since some studies have reported no changes in recovery from UVD despite a deficient nodulus, flocculus or uvula [51,52], while others have observed delayed (but not abolish) VC in case of preexisting cerebellar lesions affecting the nodulus, uvula [53] or flocculus [50,54,55].…”
Section: Cerebellar Contributionmentioning
confidence: 93%